Role of Civil Society in Growth of Populism in Europe: Exploring the relationship between civil society and populism in Europe (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Scholastic regard for populism has sharply expanded as of late. However, a commonly acknowledged definition is still lacking, with scholars differing on order, labels, and limits between its various signs. Populists claim to be the only legitimate agent of the people. Does it imply that there is no space for civil society? Populism's central and lasting account is the juxtaposition of a (degenerate) »political class,« »elite,« or »establishment,« and »the people,« as whose sole true voice the populist party bills itself. We looking at the encounters of Europe, where populist parties are on the ascent and there is a rich civil society custom.